2016
DOI: 10.1016/j.jascer.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation and AC conductivity studies of Se90Cd10−xInxglassy alloys

Abstract: Chalcogenide glassy alloys of Se 90 Cd 10−x In x (x = 2, 4, 6, 8) are synthesized by melt quench technique. The prepared glassy alloys have been characterized by techniques such as differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and energy dispersive X-ray (EDAX). Dielectric properties of Se 90 Cd 10−x In x (x = 2, 4, 6, 8) chalcogenide glassy system have been studied using impedance spectroscopic technique in the frequency range 42 Hz to 5 MHz at room temperature. It is found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The double logarithmic plot of σ ac versus frequency for the pure PVA and nanocomposite films with varying filler loadings increased gradually with increasing frequency (Figure 17). This increase in AC conductivity with increasing frequency is attributed to the enhancement in the conduction mechanism due to the hopping of charge carriers 59 . A further study of these plots revealed the existence of three separate zones.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The double logarithmic plot of σ ac versus frequency for the pure PVA and nanocomposite films with varying filler loadings increased gradually with increasing frequency (Figure 17). This increase in AC conductivity with increasing frequency is attributed to the enhancement in the conduction mechanism due to the hopping of charge carriers 59 . A further study of these plots revealed the existence of three separate zones.…”
Section: Resultsmentioning
confidence: 84%
“…This increase in AC conductivity with increasing frequency is attributed to the enhancement in the conduction mechanism due to the hopping of charge carriers. 59 A further study of these plots revealed the existence of three separate zones. The less value of electrical conductivity in low-frequency dispersion region attributes to the space-charge polarization.…”
Section: Ac Conductivitymentioning
confidence: 94%
“…Contribution of ion jumps, conduction loss of ion migration and ion polarisation losses are accountable for ɛ ″. Probably ion vibration is the only source of dielectric loss at high frequencies, therefore ε ″ is minimum at high frequencies [7].…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric study of a material helps to define and understand two basic electrical characteristics of the material, Namely, the capacitive insulating behavior and the conduction nature behavior. The first behavior represents the ability to store electrical charges, while the second represents the ability to transfer electrical charge [23].…”
Section: Complex Dielectric Constantmentioning
confidence: 99%
“…Therefore, studying the electric and dielectric properties of deliberately doped materials as a function of frequency and temperature is crucial in understanding the conduction mechanism. The conduction mechanism of such glassy systems was found to vary with varying the dopant ion type and its concentration [16][17][18][19][20][21][22][23]. In this regard, impedance spectroscopy is a powerful technique for measuring many of the electrical properties of material and their interface with electronically conducting electrodes.…”
Section: Introductionmentioning
confidence: 99%